HDR brachytherapy of skin cancer – the Wielkopolski Cancer Centre’s experience - Skowronek, Janusz; Chicheł, Adam; Piotrowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2005)
Purpose: To analyze treatment results of HDR brachytherapy (BT) in patients with skin tumors. Material and methods: 179 patients with skin tumor were treated with HDR BT in the Wielkopolski Cancer Center between May 1999 and May 2004. There were 93 men (52 %) and 86 women (48%), age ranged from 27 to 96 years (median – 70.8 years). The most frequently diagnosed tumor was squamous cell carcinoma (n=102, 57%) and basal cell carcinoma (n=52, 29%). In most of the cases, the tumor was diagnosed in an early clinical stage (T1 – n=79, 44.1%, T2 – n=60, 33.5%). HDR BT of 50 – 60 Gy in five or six fractions counted in distances 0.5 to 2 cm from the tube axis was used. Most frequently, 6 fractions of 10 Gy were used (n=110, 61.5%). Patients were observed during a period of 12 months in terms of local remission rates depending on chosen prognostic factors (age, sex, clinical stage, location, histopathology and method of treatment). Results: Complete remission (CR) assessed in 4 weeks after treatment was observed in 152/179 (84.9%) of patients, partial remission (PR) – in 16 (8.9%), no remission (NR) – in 9 (5%), progression in 1 case, respectively, 1 patient died. A significant correlation was observed between the remission rate and clinical stage, location and method of treatment (Principal Component Analysis). After 12 months, CR in 146/179 cases (81.6%), progression – in 16 cases (8.9%), were observed, respectively. Five of the patients (2.8%) died, 12 patients (6.7%) were lost (lack of information). Early complications were assessed in 4 weeks after treatment: they occurred in all cases: 1st grade in 126 cases (70.4%), 2nd – in 31 cases (17.3%) and 3rd grade – in 22 cases (12.3%), respectively. Late complications (assessed in 6 months after treatment) were observed: 1st grade (n = 66/179, 36.9%), 2nd grade (n = 21, 11.7%) and 3rd grade (n=6, 3.4%). Conclusions: 1. HDR BT is a highly effective treatment method of skin tumors. Complications rate is acceptable and treatment costs are low. 2. In some tumors (great skin lesions in the skull, near the eyes or on the nose) BT allows great dose reduction in the surrounding healthy tissues. 3. Higher remission rate is observed in tumors in lower clinical stage, treated radically and localised in the face.